BASILIC VEIN ELEVATION FOR BRACHIOBASILIC ARTERIOVANOUS FISTULAE - SINGLE OR TWO STAGE PROCEDURE - Muhammad Jamil; Rashid Usman (Journal of University Medical & Dental College)
ABSTRACT OBJECTIVES: To assess the difference in both procedures in terms of function, post operative complications and long term patency of ﬁstulae. STUDY DESIGN: Comparative observational study PLACE AND DURATION: This study was carried out at department of Vascular Surgery, Combined Military Hospital LahorefromMarch 2012 to March 2013. PATIENTS AND METHODS: 62 Brachiobasilicarteriovenous ﬁstulae (BB AVF) were created. One stage procedure was performed in 23, and two stage in 39 patients. Data including age, sex, patency, time to mature and post op complications were noted. RESULTS: Functional patency and long term patency of BB AVF was better in two stage BB AVF creation procedure. Postoperative complications especially haematoma formation and wound infection, were relatively less in two stage procedure. BB AVF patency was also better in patients who had their ﬁstulae created before the haemodialysis was started. CONCLUSION: Patency rate is better in two stage procedure for BB AVF creation and two stage procedure also has less post operative complications.